PENGARUH JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP PENERIMAAN RETRIBUSI PELAYANAN KESEHATAN KABUPATEN BERAU - Sayugo, Agus (ECO-BUILD, 2018)
This study aims to determine the population, the rate of economic growth and the amount of health service fees retribution and also to determine the effect of population and economic growth on the acceptance of health service charges. This study takes place at the District Health Office of Berau and the Central Bureau of Statistics of Berau District. The research method used is documentation study method which comes from financial report and other related documents from Berau District Health Office and Central Bureau of Statistics of Berau Regency. Proving The hypothesis of this study using the F test to test the level of significance of the influence of independent variables on the dependent variable simultaneously. The results obtained in this study is calculated F calculated by 61.34> from F table with a number of 6.94 using α = 5% so it can be concluded that the population and economic growth together have a significant effect on Acceptance of health service charges